EFEKTIVITAS PEMBELAJARAN ONLINE SAAT PANDEMI COVID-19 DI UNIVERSITAS ISLAM NEGERI AR-RANIRY BANDA ACEH - Akhiar, Akhiar; Muazzinah, Muazzinah (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2021)
The Covid-19 pandemic has changed the daily routine of work. Since the issuance of PP Number 21 of 2020 concerning Large-Scale Social Restrictions, activities in public places or public facilities have been limited with the aim of reducing the spread of Covid-19. Likewise with the learning process, the Covid-19 pandemic has changed the conventional face-to-face learning pattern to face-to-face online. Therefore, this study aims to determine how effective online learning is at UIN Ar-Raniry Banda Aceh. The research method used in this study is a qualitative method with a descriptive approach with observation, interviews and documentation techniques. The research subjects are LPM UIN Ar-Raniry as policy makers as well as lecturers and students at UIN Ar-Raniry as implementers of online learning. The results of this study indicate that online learning at UIN Ar-Raniry Banda Aceh has not been effective, but to achieve this effectiveness the campus has tried as much as possible by doing several things, namely before the implementation of online learning activities the campus first designed planning and survey conditions and training to lecturers, then formulate policies, formulate goals and strategies, determine facilities and supervision which is carried out routinely through the Siakad portal.